Comparative Evaluation of Polyester and ePTFE Vascular Grafts in Endovascular Applications: Performance, Biocompatibility, and Quality Insights - Dr. Kothwala Deveshkumar; Lad Hirenkumar; Patel Shivamkumar (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Endovascular interventions have emerged as a preferred approach for treating vascular diseases, including aneurysms and peripheral arterial disorders, due to their minimally invasive nature and reduced recovery time. Among the critical components of these procedures are synthetic vascular grafts primarily polyester and expanded polytetrafluoroethylene (ePTFE). This review evaluates the performance, structural features, clinical efficacy, and biocompatibility of both graft types. In addition to literature analysis from PubMed, Scopus, and Google Scholar, internal validation data from Meril’ ISO 13485-certified quality control (QC) laboratory were incorporated. Polyester grafts offer superior tensile strength and durability, particularly useful in large-diameter applications, whereas ePTFE provides enhanced flexibility and sealing capabilities, ideal for tortuous anatomical placements. Meril’s QC testing demonstrated favorable results for both materials in terms of reproducibility, mechanical integrity, and biocompatibility. Regulatory approvals, including CE and FDA, confirm clinical safety, although comprehensive, head-to-head randomized clinical trials are limited. This review concludes that the optimal choice between polyester and ePTFE grafts depends on patient-specific factors, anatomical complexity, and procedural objectives. Future directions include development of hybrid grafts with improved infection resistance and dynamic compliance, alongside integration of real-time imaging features.